New records and range extension of Promops centralis (Chiroptera: Molossidae) - Tania P. González-Terrazas; Luis R. Víquez; Ana Ibarra-Macías; Adrián Tonatiuh Ruíz; Leonora Torres-Knoop; Kirsten Jung; Marco Tschapka; Rodrigo A. Medellín (Revista Mexicana de Biodiversidad)
We captured Promops centralis and recorded its echolocation calls in Bahía de Kino, Sonora, which represents the first record of this species for the state of Sonora, Mexico. Our new record extends the distribution of P. centralis at least 1,300 km northwest from the northernmost known locality, Cuautla, Jalisco. Until now, there was no evidence of the occurrence of P. centralis in the deserts of northern Mexico. These new records are ecologically significant as they show that this species also occurs in extreme dry areas such as the Sonoran Desert. Our findings suggest that P. centralis may be more widely distributed than previously thought.